Birds Kept in the German Zoo “Tierpark Berlin” Are a Common Source for Polyvalent Yersinia pseudotuberculosis Phages - Hammerl, Jens Andre; Barac, Andrea; Bienert, Anja; Demir, Aslihan; Drüke, Niklas; Jäckel, Claudia; Matthies, Nina; Jun, Jin Woo; Skurnik, Mikael; Ulrich, Juliane; Hertwig, Stefan (Frontiers in Microbiology, 2022)
Yersinia pseudotuberculosis is an important animal pathogen, particularly for birds, rodents and monkeys, which is also able to infect humans. Indeed, an increasing number of reports have been published on zoo animals that were killed by this species. One option to treat diseased animals is the application of strictly lytic (virulent) phages. However, thus far relatively few phages infecting Y. pseudotuberculosis have been isolated and characterized. To determine the prevalence of Y. pseudotuberculosis phages in zoo animals, fecal samples of birds and some primates, maras and peccaries kept in the Tierpark Berlin were analysed. Seventeen out of 74 samples taken in 2013 and 2017 contained virulent phages. The isolated phages were analysed in detail and could be allocated to three groups. The first group is composed of ten T4-like phages (PYps2T group: Myoviridae; Tevenvirinae; Tequatrovirus), the second group (PYps23T group: Chaseviridae; Carltongylesvirus; Escherichia virus ST32) consists of five phages encoding a podovirus-like RNA-polymerase that are related to an uncommon genus of myoviruses (e.g. E. coli phage phiEcoM-GJ1), while the third group is comprised of two podoviruses (PYps50T group: Autographiviridae; Studiervirinae; Berlinvirus) which are closely related to T7. The host range of the isolated phages differed significantly. Between 5.5% and 86.7% of 128 Y. pseudotuberculosis strains belonging to 20 serotypes were lysed by each phage. All phages were additionally able to lyse Y. enterocolitica B4/O:3 strains, when incubated at 37°C. Some phages also infected Y. pestis strains and even strains belonging to other genera of Enterobacteriaceae. A cocktail containing two of these phages would be able to lyse almost 93% of the tested Y. pseudotuberculosis strains. The study indicates that Y. pseudotuberculosis phages exhibiting a broad host range can be isolated quite easily from zoo animals, particularly birds.